Analisis del recaudo del impuesto de industria y comercio en el sector hotelero de la ciudad de Santa Marta - Gil Caballero, Brenda; Lajud Torregrosa, Bridney (Universidad Antonio Nariño, 2023)
Tax collection is a fundamental piece of municipalities and districts' finances since it enables the execution of development plans that have been proposed by the public administration. Therefore, it is understood that taxes are true allies of development and help address the needs of the community to which they belong. Among these taxes, there is the Industry and Commerce Tax, considered one of the most important, if not the most important, considering the primary economic activities of the area where they are collected. "Colombian municipalities receive transfers from the nation, most of them with specific purposes. In addition to this, they need to generate their own income through efficient tax collection management, with the aim of making the municipality selfsustainable. Consequently, this enables them to reduce their dependence on the transfers granted by the national government" (LUGO MORA & MUÑOZ DELGADO, 2022). The city of Santa Marta, located in the Magdalena department in northern Colombia, is a city that has focused its industry and economy on tourism and all the commercial activities derived from it, in addition to other sectors that have made an impact in the region, such as mining, fishing, agriculture, the growing industry, and port activities. This is why the Industry and Commerce Tax is considered the most important in the city of Santa Marta, considering the commercial activity of the hotel sector, which is present throughout its territory, as well as activities such as tours, tourism companies, tour guides, among others.In the year 2020, the COVID-19 pandemic hit, and all businesses were forced to close their doors, leading to an economic crisis in the tourism and hotel sector due to the lack of income from the absence of tourists in the city streets. The situation extended until the year 2022, and one of the major affected areas was the collection of the Industry and Commerce Tax, as well as district finances and the development of the administration's development plans. It is relevant to understand the behavior of the Industry and Commerce Tax during the period from 2020 to 2022, considering the social, health, and economic conditions during these years. For this reason, the decision was made to carry out the present research, using a descriptive study methodology with a qualitative approach, applying instruments such as interviews with key individuals in the sector. This allows for a deeper understanding of the situation experienced by those involved in the hotel, tourism, and tax collection sectors.